Da'wah Communication Strategies in Dealing with Online Gambling among Teenagers - M. Nashoihul Ibad; Dito Anurogo; Novianto Puji Rahardjo (Feedback International Journal of Communication, 2024)
Online gambling has become a serious problem that threatens the younger generation, especially teenagers. "Online gambling has serious psychological impacts, such as stress, depression, and social isolation, and has the potential to trigger criminal acts. Online gambling addiction can damage many aspects of a teen's life, including mental health, social relationships, academic achievement, and financial stability. This research aims to formulate an effective da'wah communication strategy to overcome these problems. This qualitative research is carried out using a case study approach. The results of the study show that a combination of personal, community, and social media approaches is an effective da'wah communication strategy in dealing with online gambling among teenagers. An individual approach through counseling and mentoring can provide emotional and spiritual support to adolescents who are involved in online gambling. The community approach consists of working with religious leaders, community leaders, and educational institutions to create an environment that supports a healthy lifestyle and is free from gambling. Meanwhile, the social media approach can be used to spread positive messages and anti-gambling campaigns more widely. In addition, this research also enriches the understanding of the importance of integration between traditional and modern communication in the context of da'wah. Keywords:  Communication Strategies, Da'wah Communication, Online Gambling, Teenagers